Intensive LDL cholesterol-lowering treatment beyond current recommendations for the prevention of major vascular events: a systematic review and meta-analysis of randomised trials including 327 037 participants. Issue 1 (January 2020) - Wang, Nelson; Fulcher, Jordan; Abeysuriya, Nishan; Park, Laura; Kumar, Shejil; Di Tanna, Gian Luca; Wilcox, Ian; Keech, Anthony; Rodgers, Anthony; Lal, Sean
Summary: Background: The benefits of LDL cholesterol-lowering treatment for the prevention of atherosclerotic cardiovascular disease are well established. However, the extent to which these effects differ by baseline LDL cholesterol, atherosclerotic cardiovascular disease risk, and the presence of comorbidities remains uncertain. Methods: We did a systematic literature search (MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials, from inception up to June 15, 2019) for randomised controlled trials of statins, ezetimibe, and proprotein convertase subtilisin/kexin type 9 inhibitors with at least 1000 patient-years of follow-up. Random-effects meta-analysis and meta-regressions were done to assess for risk of major vascular events (a composite of cardiovascular mortality, non-fatal myocardial infarction, non-fatal ischaemic stroke, or coronary revascularisation) per 1 mmol/L (38·7 mg/dL) reduction in LDL cholesterol concentrations. Findings: 327 037 patients from 52 studies were included in the meta-analysis. Each 1 mmol/L reduction in LDL cholesterol was associated with a 19% relative risk (RR) reduction for major vascular events (RR 0·81 [95% CI 0·78–0·84]; p<0·0001). Similar reductions (per 1 mmol/L reduction in LDL cholesterol) were found in trials with participants with LDL cholesterol 2·60 mmol/L or lower, 2·61–3·40 mmol/L, 3·41–4·10 mmol/L, and more than 4·1 mmol/L (p=0·232 for interaction); and in a subgroup of patients who all had a baseline LDL cholesterol less than 2·07 mmol/L (80 mg/dL; RR 0·83 [95% CI 0·75–0·92]; p=0·001). We found greater RR reductions in patients at lower 10-year atherosclerotic cardiovascular disease risk (change in RR per 10% lower 10-year atherosclerotic cardiovascular disease 0·97 [95% CI 0·95–0·98]; p<0·0001) and in patients at younger age across a mean age of 50–75 years (change in RR per 10 years younger age 0·92 [0·83–0·97]; p=0·015). We found no difference in RR reduction for participants with or without diabetes (p=0·878 for interaction) and chronic kidney disease (p=0·934 for interaction). Interpretation: For each 1 mmol/L LDL cholesterol lowering, the risk reduction of major vascular events is independent of the starting LDL cholesterol or the presence of diabetes or chronic kidney disease. Patients at lower cardiovascular risk and younger age might have a similar relative reduction in risk with LDL-cholesterol lowering therapies and future studies should investigate the potential benefits of earlier intervention. Funding: None.